2021
DOI: 10.3390/jcm10081656
|View full text |Cite
|
Sign up to set email alerts
|

Admission High-Sensitive Cardiac Troponin T Level Increase Is Independently Associated with Higher Mortality in Critically Ill Patients with COVID-19: A Multicenter Study

Abstract: Background: In coronavirus disease 2019 (COVID-19) patients, increases in high-sensitive cardiac troponin T (hs-cTnT) have been reported to be associated with worse outcomes. In the critically ill, the prognostic value of hs-cTnT, however, remains to be assessed given that most previous studies have involved a case mix of non- and severely ill COVID-19 patients. Methods: We conducted, from March to May 2020, in three French intensive care units (ICUs), a multicenter retrospective cohort study to assess in-hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…As shown in Figure 2 , the frequency of myocardial injury varies widely probably in relation to patient selection. In studies of patients admitted to Intensive Care Units (ICU), the frequency of myocardial injury is as high as or >50% 32 , 46 , 47 . Studies that include a broader spectrum of patients suggest a frequency that ranges from 10% 48 , 49 to more than 45% 26 , 27 , 50 , 51 , 52 .…”
Section: Frequency Of Myocardial Injury In Covid-19 Patientsmentioning
confidence: 99%
“…As shown in Figure 2 , the frequency of myocardial injury varies widely probably in relation to patient selection. In studies of patients admitted to Intensive Care Units (ICU), the frequency of myocardial injury is as high as or >50% 32 , 46 , 47 . Studies that include a broader spectrum of patients suggest a frequency that ranges from 10% 48 , 49 to more than 45% 26 , 27 , 50 , 51 , 52 .…”
Section: Frequency Of Myocardial Injury In Covid-19 Patientsmentioning
confidence: 99%
“… 136 Several other studies have confirmed the relationship between high troponin values and a worse prognosis in patients with COVID‐19 infection. 126 , 137 , 138 , 139 It is still not clear whether this relationship is due to a more severe form of COVID‐19 or to a more extensive cardiac damage or both. 135 Troponin elevation during SARS‐COV‐2 infection can be underpinned by several causes.…”
Section: Covid‐19 Infection and Cardiac Biomarkersmentioning
confidence: 99%
“…In another recently published article, high concentrations of CK‐MP, procalcitonin, NT‐proBNP, BNP, troponin, and D‐dimers have been shown to predict severity and survival for patients with COVID‐19 as well 136 . Several other studies have confirmed the relationship between high troponin values and a worse prognosis in patients with COVID‐19 infection 126,137–139 . It is still not clear whether this relationship is due to a more severe form of COVID‐19 or to a more extensive cardiac damage or both 135 .…”
Section: Covid‐19 Infection and Cardiac Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations